Appreciation of Peer Reviewers for 2017. (27th October 2018) - Florindo, Fabio; Moldwin, Mark; Okin, Gregory; Robock, Alan; Rohling, Eelco J.; Halekas, Jasper S.
Abstract: On behalf of the authors and readers of Reviews of Geophysics, the American Geophysical Union, and the broader scientific community, the Editors wish to wholeheartedly thank those who reviewed the manuscripts for Reviews of Geophysics in 2017. The journal could not exist without your investment of time and effort, lending your expertise to ensure that the papers published in this journal meet the standards that the research community expects for it. We sincerely appreciate all that you do, and we are very grateful for your willingness and readiness to serve in this role. Plain Language Summary: On behalf of the authors and readers of Reviews of Geophysics, the American Geophysical Union, and the broader scientific community, the Editors wish to wholeheartedly thank those who reviewed the manuscripts for Reviews of Geophysics in 2017. The journal could not exist without your investment of time and effort, lending your expertise to ensure that the papers published in this journal meet the standards that the research community expects for it. We sincerely appreciate all that you do, and we are very grateful for your willingness and readiness to serve in this role. Reviews of Geophysics published 29 review papers, a commentary and an editorial in 2017, covering most of the AGU Section topics, and for this we were able to rely on the efforts of 99 dedicated reviewers. Many reviewers answered the call multiple times. Thank you again. We look forward to a 2018 of exciting advances in the field and communicating those advances to our community and to the broader public. Key Point: The Reviews of Geophysics Editors thank all the peer reviewers from 2017